The Relationship between the Mite, Eriophyes vitis (Pagst.) and Leaf Curl on Vitis vinifera L. cv. Shiraz - Schwartz, A.; Deklerk, C. A. (South African Journal of Enology and Viticulture, 2017)
Eriophyes vitis (Pagst.) is known as the grape erineum or blister mite. The distribution of the erineum mite is world wide, being a pest of grapevines in nearly every vine growing country. Three physiologically distinct strains of the mite are reported, each characterised by the type of injury produced: the bud strain (which causes stunted growth), the erineum or blister strain (blisters with abnormal hairs) and the leaf-curling strain (distinct leaf curl) (Jeppson, Keifer & Baker, 1975).